2016
DOI: 10.1016/j.bcmd.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

JAK2V617F-mutant vascular niche contributes to JAK2V617F clonal expansion in myeloproliferative neoplasms

Abstract: The myeloproliferative neoplasms (MPNs) are characterized by hematopoietic stem/progenitor cell (HSPC) expansion and overproduction of blood cells. The acquired mutation JAK2V617F plays a central role in these disorders. Mechanisms responsible for MPN HSPC expansion is not fully understood, limiting the effectiveness of current treatments. Endothelial cells (ECs) carrying the JAK2V617F mutation can be detected in patients with MPNs, suggesting that ECs are involved in the pathogenesis of MPNs. Here we report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 57 publications
4
54
0
Order By: Relevance
“…Results from our previous studies and current work provide the first evidence that TPO and MPL have important role(s) in the vascular niche function and altered TPO/MPL signaling can contribute to JAK2V617F‐bearing MK‐induced HSPC expansion via its effect on the vascular niche function. First, we demonstrated that the EC MPL receptor is important for the maintenance/expansion of the JAK2V617F clone over the JAK2WT clone in vitro . Second, we showed that TPO and MPL are important for the expression of key vascular niche factor CXCL12 in marrow ECs in vivo.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Results from our previous studies and current work provide the first evidence that TPO and MPL have important role(s) in the vascular niche function and altered TPO/MPL signaling can contribute to JAK2V617F‐bearing MK‐induced HSPC expansion via its effect on the vascular niche function. First, we demonstrated that the EC MPL receptor is important for the maintenance/expansion of the JAK2V617F clone over the JAK2WT clone in vitro . Second, we showed that TPO and MPL are important for the expression of key vascular niche factor CXCL12 in marrow ECs in vivo.…”
Section: Discussionmentioning
confidence: 82%
“…Previously, using an in vitro competitive growth assay in which both JAK2WT and JAK2V617F HSPCs were cultured together in the presence of conditioned medium collected from WT or MPL −/− murine ECs, we found that there were significantly more JAK2WT cells than JAK2V617F cells in the presence of MPL −/− EC conditioned medium compared to in WT EC conditioned medium, suggesting that the EC MPL receptor is important for the maintenance/expansion of the JAK2V617F cells over JAK2WT cells [42]. These observations led us to hypothesize that some secreted factors from vascular ECs contribute to the JAK2V617F clonal expansion in MPNs, and that TPO/MPL signaling is critical for this vascular niche function.…”
Section: Tpo/mpl Signaling Contributes To the Jak2v617f-bearing Mk-inmentioning
confidence: 95%
“…[14][15][16] The JAK2 V617F mutation expands the perivascular niche Next, we attempted to determine the cellular basis of how the JAK2 V617F mutation alters ECs to promote neoplastic hematopoiesis in MPNs. First, we found that the JAK2 V617F ECs (isolated from the lungs of Tie2 + /FF1 + mice) displayed significantly increased cell proliferation, wound closure (as a measure of cell migration), tube formation (as a measure of angiogenesis), and decreased apoptosis (after irradiation) compared with normal ECs in vitro, 10 indicating that the kinase mutant might act to expand the vascular niche in JAK2 V617F -positive Tie2 + /FF1 + mice, and alters its function, findings that also characterize the marrow of patients with MPNs. [17][18][19] Based on the known chemokine-and cytokinemediated mechanisms by which C-X-C motif chemokine ligand 12 (CXCL12)-abundant reticular (CAR) niche cells support hematopoiesis, we then measured the expression levels of CXCL12 and stem cell factor (SCF), the two essential niche factors important for HSC maintenance and survival, [20][21][22][23] in freshly isolated marrow ECs from normal and Tie2 + /FF1 + mice.…”
Section: The Jak2 V617f -Positive Ecs Protect Jak2 V617f Hscs From Ramentioning
confidence: 90%
“…In contrast, JAK2 V617F Lin − /cKit + cells displayed a relative growth advantage over the corresponding normal Lin − /cKit + cells when cocultured on JAK2 V617F -positive ECs. 10 These results suggested that the malignant niche differentially supports the proliferation of malignant stem cells over normal cells.…”
Section: The Jak2 V617f Vascular Niche Promotes Jak2 V617f -Mutant CLmentioning
confidence: 93%
See 1 more Smart Citation